Jogos virtuais: um caminho para a aprendizagem do Ensino de História - Josimar de Mendonça (2016)
Current research aims to investigate the learning processes present in free online games, online and accessible by mobile devices. Since in the last decades, the advent of Digital Information and Communication Technologies (TDICs) has made possible new perspectives for learning the content of History for students who are present subjects in contemporary society. The objective of this research is to investigate the historical characteristics that permeate free online games, accessible online and accessible by mobile devices that use historical themes. For the development of this study, the methodological approach used involved a qualitative approach and content analysis, concomitantly with a textual survey about the learning present in digital games. As a mandatory requirement for approval in the Professional Master's Program Education and Teaching - PROMESTRE will be elaborated, in the end, a content that aims to highlight the basic fundamentals of free online games, online and accessible by selected mobile devices and demonstrate some possibilities of Their use, inside and outside the school environment, in order to promote the learning of the curricular content of History. This content will be available as an e-book for downloads.